The Effect of Arm Muscle Power Abilities on Badminton Backhand Smash: A Systematic Review - Situmorang, Cristeven Tono; Zalukhu, Fans Darno Prianto Osra; Ginting, Risky Cristyan; Gea, Dedi Torman; Manik, Penata (Jurnal Inovasi Olahraga, 2025)
Research Objectives: This study aimed to systematically review the influence of arm muscle power on badminton backhand smash performance and to identify methodological trends, limitations, and directions for future research.Materials and Methods: Following PRISMA guidelines, electronic searches of PubMed, Scopus, Web of Science, and SPORTDiscus (2010–2025) were conducted. A total of 1,053 records were screened, and 20 studies met the inclusion criteria. Eligible studies included experimental, correlational, and biomechanical investigations focusing on the relationship between upper-limb power and backhand smash performance. Data extraction and quality appraisal were performed independently by two reviewers.Results: The synthesis of 20 studies (N = 1,245) revealed consistent evidence of strong positive associations (r = 0.72–0.95) between upper-limb explosive power and smash velocity, accuracy, or overall effectiveness. Biomechanical analyses highlighted the critical role of the wrist-forearm segment in accelerating racket head speed. Training interventions incorporating resistance, plyometric, and medicine-ball drills led to significant performance gains, with smash velocity improvements ranging from 6–12% over 6–8 weeks. Limitations included heterogeneous power-testing protocols and a lack of longitudinal studies.Conclusions: Arm muscle power plays a decisive role in optimizing badminton backhand smash performance. Coaches should prioritize targeted upper-limb power training, particularly wrist-forearm conditioning, while researchers should pursue standardized, longitudinal studies to deepen causal understanding and refine training strategies.